2017
DOI: 10.1093/ntr/ntw397
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Cessation Interventions in Tertiary Hospitals in Nigeria: An Audit of Patient Records

Abstract: This study provides empirical evidence showing that there is poor documentation of tobacco use inquiry and brief intervention among physicians in tertiary hospitals in Nigeria. Records showing implementation of the 5A's were abysmally low and opportunities for brief intervention may have been missed. In line with the World Health Organization recommendations of Article 14 of the Framework Convention on Tobacco Control, efforts to promote brief intervention among physicians in tertiary hospitals in Nigeria shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…There are myriads of oral diseases associated with chronic tobacco use 3,4 including gingivitis, periodontitis, periodontal abscess, oral pre-cancer, and oral cancer 3,4 .…”
Section: Commentarymentioning
confidence: 99%
See 4 more Smart Citations
“…There are myriads of oral diseases associated with chronic tobacco use 3,4 including gingivitis, periodontitis, periodontal abscess, oral pre-cancer, and oral cancer 3,4 .…”
Section: Commentarymentioning
confidence: 99%
“…A review of clinical cases of oral diseases managed in dental settings revealed that patients with a history of tobacco use had poorer health outcomes than patients that were non-users of tobacco [5][6][7] . A very effective way to stem the development of tobacco-associated oral diseases is through tobacco cessation interventions 3 .…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations